INFLUENCE OF INDONESIAN PRODUCT PLACEMENT IN KOREAN DRAMA SERIES TO BUY INTEREST THROUGH BRAND FAMILIARITY AS A MEDIATOR - Ribka Xena Sitorus; La Mani; Diyandra Oktiano; Yuanita Amalia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Purpose: This study was to determine the effect of Kopiko product placement in Vincenzo's Korean drama on buying interest through Kopiko brand familiarity with Indonesian audiences. Research design, Data, and Methodology: This study uses quantitative shared in the chat group Open Chat Line Song Joong Ki. This study was conducted through a questionnaire using google form which was sent to 181 respondents who were members of the open chat Line group Song Joong Ki fans who were domiciled in DKI Jakarta. Results: The results of the study stated that there is a positive and significant influence between product placement and interest in buying through brand familiarity as a mediating variable. Conclusion: Vincenzo's drama series succeeded in maximising the effect of product placement of Kopiko’s product especially in interest in buying through brand familiarity as the mediating variable.Vincenzo's drama series succeeded in maximising the effect of product placement of Kopiko’s product especially in interest in buying through brand familiarity as the mediating variable. The presence of Kopiko in the Korean drama series can foster buying interest in these local candy products to Korean drama audiences in Indonesia. For marketers of Indonesian products, this research can be a reference for companies to start marketing their products indirectly through product placement strategies in Korean drama series. Product placement in Korean drama series is generally not done blatantly, this makes the advertised products do not interfere with the storyline of the drama series but still make an impression on the audience.